2002
DOI: 10.1128/iai.70.9.5185-5192.2002
|View full text |Cite
|
Sign up to set email alerts
|

The YeastCandida albicansBinds Complement Regulators Factor H and FHL-1

Abstract: The human facultative pathogenic yeast Candida albicans causes mucocutaneous infections and is the major cause of opportunistic fungal infections in immunocompromised patients. C. albicans activates both the alternative and classical pathway of the complement system. The aim of this study was to assay whether C. albicans binds human complement regulators in order to control complement activation at its surface. We observed binding of two central complement regulators, factor H and FHL-1, from normal human seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 51 publications
1
102
0
Order By: Relevance
“…In addition to inhibition of the alternative pathway, several bacteria (e.g., Moraxella catarrhalis, S. pyogenes, E. coli K1, and H. influenzae) bind C4BP and are shielded against the classical and lectin pathways (49 -51). Interestingly, many species, C. albicans, Borrelia recurrentis, and S. pyogenes, among others, have been shown to bind both FH and C4BP (26,(52)(53)(54)(55). We have recently demonstrated that non-typeable H. influenzae binds C4BP (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inhibition of the alternative pathway, several bacteria (e.g., Moraxella catarrhalis, S. pyogenes, E. coli K1, and H. influenzae) bind C4BP and are shielded against the classical and lectin pathways (49 -51). Interestingly, many species, C. albicans, Borrelia recurrentis, and S. pyogenes, among others, have been shown to bind both FH and C4BP (26,(52)(53)(54)(55). We have recently demonstrated that non-typeable H. influenzae binds C4BP (30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences in FHL-1-binding, the two Hib strains 541 and 539 showed similar survival when exposed to human serum, further suggesting the importance of FH binding in serum resistance. C. albicans is another pathogen interacting with FH via two binding sites (26). The first binding domain of C. albicans is located in SCRs 6 and 7 and the second in SCRs 19 and 20.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other pathways by which pathogens exploit the complement system as a means to escape the host immune response. [18][19][20][21][22][23] For example, HIV has evolved to exploit complement pathways to survive and promote transmission to permissive cells. 24 In order for systemic delivery of Ad vectors to achieve clinical practicality, a better understanding of innate immunity is needed, including how complement influences the transduction process.…”
Section: Complement and Liver Transduction By Adenovirus Kr Zinn Et Almentioning
confidence: 99%
“…S. aureus, Trypanosoma cruzi, and Pseudomonas aeruginosa) (17,(32)(33)(34) or indirect mechanisms by targeting and manipulating the host endogenous C3-inhibitor, Factor H (or Factor H-like proteins) (e.g. Borrelia burgdorferi, Candida albicans, and Streptococcus pyogenes) (35)(36)(37)(38). A parallel strategy employed primarily by intracellular pathogens involves membrane proteins with C3 binding capabilities that facilitate cellular internalization via the complement receptors (CR1 or CR2) (e.g.…”
mentioning
confidence: 99%